Perspektif Hadis Nabi Saw Mengenai Kebersihan Lingkungan - Anita Agustina (Jurnal Penelitian Ilmu Ushuluddin, 2021)
This study aims to discuss the hadith perspective on cleanliness. This research is a qualitative type by applying literature study to interpret the hadith about cleanliness with a content analysis approach. The results and discussion of this study include the notion of cleanliness, hadiths regarding cleanliness, and cleanliness in the hadith perspective. This study concludes that maintaining cleanliness is very important for daily life including physical and spiritual cleanliness and environmental cleanliness. This study recommends all parties to maintain cleanliness which is not only related to ethics but also the value of worship, especially the recommended importance of implementing hygiene habits from an early age through the role of Islamic institutions.